(3GdOQI GdaQjOI aj TQM GdbUjOIs - (3efJLH GdOjf CHhGdYR Hf GdQTjO GdgeOGfj GdebQjs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3ShQI Bd YeQGf eOfjI hgj eGFJG BjI s
(3BNQgG (B:s
(3aaJMgG fGaY hCScfgG GdHGbhf hCf jhJjf NjQkG s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs